REFERRED OTALGIA – A CASE SERIES - R, Sumitha; Joseph, Nisha Alice (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Introduction: Referred otalgia is a challenging symptom, with the burden on the physician to identify the source. It is a pain originating outside the ear. This is caused by the complex nervous connections in the head and neck areas, the ear, the pharynx and the nose. Aim: To study the possible aetiologies of referred otalgia and to formulate an appropriate management plan. Materials and Methods: This prospective study was conducted on patients presenting to ear, nose, and throat (ENT) outpatient department in Sree Balaji Medical College and Hospital, Chennai, with complaint of ear ache either unilateral or bilateral from which patients who had referred otalgia were evaluated after taking an informed consent. The patient's details were recorded, and a detailed history of their complains was taken. A thorough clinical evaluation was done to know the possible aetiology Results: Of 870 patients who presented with an ear ache, 103 (11.9%) patients had referred otalgia. The most common cause for referred otalgia from this study was found to be temporomandibular joint (TMJ) dysfunction in 38 (36.9%) patients, followed by dental problems in 32 patients (31.06%). Conclusion: Referred otalgia has been a well-documented phenomenon in the ENT and neurosurgical literature. One has to be knowledged about the neuroanatomy and sensory innervations of the ear and the dermatomal sites in order to know the primary cause of the earache. TMJ disorders and dental causes for referred otalgia are very important factors and should always be evaluated for any such case. Keywords: Referred, Otalgia, Ear ache.